Bandwidth Estimation Algorithm of WestwoodNR for Wireless Network - Vyomal N, Pandya; Reddy, P. Rahul; Choubey, Abhishek (International Journal of Engineering and Technology, 2018)
Two widely known parameters of Transmission Control Protocol (TCP) used to control the flow of packets are Congestion Window (cwnd)Â & Slow Start Threshold (ssthresh). After congestion, slow start phase or fast-retransmit phase come in action wherein TCP has an important role in the reduction of these parameters. This is in response to packet loss identified by TCP. This in turn will cause unnecessary reduction of data flow & degradation of TCP throughput. Researchers have developed some algorithms to come out of this problem, WestwoodNR is one of them. WestwoodNR is using Bandwidth Estimation algorithm to estimate available bandwidth, to make effective use of available network capacity even after the congestion episode. It allows higher values of ssthresh & cwnd when it enters the fast-retransmit phase and slow start phase. In turn this algorithm claims better performance in terms of bandwidth utilization. The focus of this paper is on error recovery mechanisms suitable for WestwoodNR operating over the wireless sub path. These mechanisms have to address the increased bit error probability and temporary disruptions of wireless links. The efficiency of WestwoodNR within wireless scenarios is investigated and possible modifications that lead to higher performance are pointed out.